Aspek-Aspek Yang Berpengaruh Dalam Penggunaan E-Filling Administrasi Perpajakan Dan Dampaknya Terhadap Kepuasan Wajib Pajak - Amilin, Ana Nurjanah (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2014)
The purposes of this study to analyze the influence of easy of use, usefulness, security and privacy to taxpayer’s satisfaction in e-filing using. The population of this research is Corporate Taxpayers. Primary data used in this study collected by the questionnaire in Jakarta Area. Convenience sampling method used in this study.There are any 86 from 88 questionnaires are feasible to analyzed. The multiple regression analysis used to test the hyphotesis. The result of this study showed that easy of use, usefulness, security and privacy positively influence and significant to taxpayer’s satisfaction.